2023
DOI: 10.1039/d2qm01201d
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth-based MOFs for photo/electrocatalysis

Abstract: Metal-organic frameworks (MOFs) material are a kind of porous crystal material, which have been studied and applied in the field of energy storage, catalysis and separation. Rare earth MOFs are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 208 publications
1
18
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40] The unique 4fsubshell electron configuration, flexible valence states, and strong spin-orbital effect of RE elements can offer great potential for tuning the electronic structures and improving the electrocatalytic performance of various TM-based catalysts. [41][42][43][44] For example, Sun et al found that the combination of Yb 2 O 3 and Ni can reduce the energy barrier of water dissociation and enlarge the active-site density, which greatly enhances the HER performance of Ni. 45 Li et al demonstrated that the co-doping of Y and Ce into Ni-MOF can finely tailor the electronic structure of NiYCe-MOF/NF by a bimetallic synergistic effect, resulting in greatly enhanced HER and OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] The unique 4fsubshell electron configuration, flexible valence states, and strong spin-orbital effect of RE elements can offer great potential for tuning the electronic structures and improving the electrocatalytic performance of various TM-based catalysts. [41][42][43][44] For example, Sun et al found that the combination of Yb 2 O 3 and Ni can reduce the energy barrier of water dissociation and enlarge the active-site density, which greatly enhances the HER performance of Ni. 45 Li et al demonstrated that the co-doping of Y and Ce into Ni-MOF can finely tailor the electronic structure of NiYCe-MOF/NF by a bimetallic synergistic effect, resulting in greatly enhanced HER and OER performance.…”
Section: Introductionmentioning
confidence: 99%
“…148 Lin et al also prepared hollow porous carbon in cages co-doped with Co and N via zeolitic imidazolium salt framework (ZIF)-triggered rapid polymerization of dopamine for efficient ORR and OER electrocatalysts. 149 Even though MOFs and COFs with unique structures and properties have been investigated as efficient electrocatalysts for oxygen evolution reaction (OER), hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), CO 2 reduction reaction (CO 2 RR), selective oxidation of organics, etc., [150][151][152][153] the MOF/COF composites have been rarely reported as electrocatalysts.…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
“…149 Even though MOFs and COFs with unique structures and properties have been investigated as efficient electrocatalysts for oxygen evolution reaction (OER), hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), CO 2 reduction reaction (CO 2 RR), selective oxidation of organics, etc. , 150–153 the MOF/COF composites have been rarely reported as electrocatalysts.…”
Section: Electrocatalytic Applicationsmentioning
confidence: 99%
“…11,12 However, the use of metal catalysts is limited due to their high cost, uncertainty in terms of long-term availability and sustainability, poor selectivity, low durability, susceptibility to gas poisoning, and negative environmental impact, hindering their application in industry. 13 To overcome the limitations of traditional metal catalysts, a variety of metal-containing porous materials, specifically covalent-organic frameworks (COFs), 14,15 and metal-organic frameworks (MOFs), 16,17 have been widely explored as effective CO 2 sorption materials, and, more recently, also as materials for conversion. However, many obstacles remain in the development of the CO 2 capture and conversion processes, including the design of stable and metal-free materials with high CO 2 adsorption abilities and selectivity, effective CO 2 conversion under benign conditions, affordability and recyclability.…”
Section: Introductionmentioning
confidence: 99%